(untitled) (Rudarsko-geološko-naftni zbornik, 2023)
West Java Province has a high potential for susceptibility to landslides. West Bandung Regency is one of the regions in West Java which has high occurrences of landslides triggered by rainfalls. Rainfall-induced landslides in this region have occurred 165 times during rainfall in the last ten (10) years. An effort to predict the landslide occurrences in this region requires the knowledge of factors affecting the hillslope stability. This paper aims to (1) evaluate the parameters affecting slope stability, (2) determine rainfall characteristics affecting slope, and (3) evaluate the performance of TRIGRS modelling. This study applies a deterministic method using the model of TRIGRS to analyze the effect of one-day antecedent rainfall intensity on the instability of hillslopes. The parameters used in this study are based on field investigation, geological and topographical maps, soil engineering properties, and historical rainfall data. The effect of one-day antecedent rainfall intensity was considered in two scenarios, i.e. 6 hours and 12 hours of antecedent rainfall. Modelling results show that hillslope instability in the study areas is affected by many factors, such as hilly morphology, steep slopes, low shear strength parameters, weathering of volcanic rocks, and the lineament density of geological structures. The modelling simulation also indicates that landslide occurrences in this study area are initiated by a long antecedent rainfall period. Based on ROC analysis, the TRIGRS model shows that the model performance evaluation is in good agreement for modelling slope stability against actual landslide events.